1994
DOI: 10.1021/ef00043a017
|View full text |Cite
|
Sign up to set email alerts
|

Iron-based catalysts for coal/waste oil coprocessing

Abstract: Coprocessing coal with waste oil can achieve the dual purpose of recycling waste oil and liquefying coal economically. Waste oil is primarily paraffinic and is a poor hydrogen donor solvent but contains dispersant additives which could help improve dispersion of the coal particles and the catalysts during liquefaction. The initial coprocessing studies were conducted using 10 % coal in tubing bomb reactors and a jet-loop reactor system developed at Auburn University. Coal conversions in excess of 85 % were obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 1 publication
0
27
0
Order By: Relevance
“…Thus, compounds of these metals may contribute to the dark color of used motor oil. Sanjay et al (2) showed that waste lubricating oil used in their study consisted of even more elements. The additional elements that they found were As, Ba, Co, Cr, Mn, Mo, and P. These differences relative to our data may be due to the fact that the waste oil used in their study was not solely composed of used motor oil but contained other waste lubricating oils as well.…”
Section: Percentage (%)mentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, compounds of these metals may contribute to the dark color of used motor oil. Sanjay et al (2) showed that waste lubricating oil used in their study consisted of even more elements. The additional elements that they found were As, Ba, Co, Cr, Mn, Mo, and P. These differences relative to our data may be due to the fact that the waste oil used in their study was not solely composed of used motor oil but contained other waste lubricating oils as well.…”
Section: Percentage (%)mentioning
confidence: 99%
“…The reason that used motor oil forms an emulsion fairly easily with detergent solutions compared to other common oily soils may be the presence of dispersant additives in the motor oil, since it is known that waste oils contain dispersant additives (2). These additives might aid the high viscosity-emulsion formation of used motor oil in detergent solutions, and hence, decrease detergency.…”
Section: Percentage (%)mentioning
confidence: 99%
See 1 more Smart Citation
“…They have pointed out that the dispersant additives presented in the waste oil were believed to enhance the coal conversion. The primary role of the dispersant additive is believed to increase coal dispersion and dissolution [26]. Further, the present results indicated that the degradation of oil sludge with additives can be carried out at a lower temperature to achieve the same degradation (conversion), in contrast to the degradation without additives.…”
Section: Effects Of Additives On Conversion Of Pyrolysis Of Oil Sludgementioning
confidence: 60%
“…Because the oil sludge is liquid type in 378-743 K [2], the additives have the dispersant effects. Sanjay et al [26] evaluated the role of a dispersant in coal liquefaction using a mineral oil as the solvent and with different concentrations of a commercial dispersant additive (HiTEC 7049, a proprietary mixture supplied by Ethyl Corp.) added to the reaction mixture. They have pointed out that the dispersant additives presented in the waste oil were believed to enhance the coal conversion.…”
Section: Effects Of Additives On Conversion Of Pyrolysis Of Oil Sludgementioning
confidence: 99%